Peer Feedback for Learning Mathematics. Issue 7 (9th August 2018) - Reinholz, Daniel L.
Abstract: This article describes Peer-Assisted Reflection (PAR), a cycle for engaging students with rich mathematical problems. PAR gives students an opportunity to receive peer feedback and revise their work, supporting sustained mathematical engagement. PAR can be incorporated into nearly any course to address logistical constraints that limit how much feedback an instructor can provide. Strategies for using PAR and sample problems are provided.